The combination of restoration of the tooth with the correction of the marginal gingival. A clinical case - Lutskaya, I.; Beloivanenko, I. (Actual Dentistry, 2018)
Summary. Describes a clinical case of re-treatment lateral incisor with defective sealing, in combination with the violation of the size and shape of the tooth. According to the situation it is planned to manufacture the veneer with a preliminary correction of the gingival margin. The combination of aesthetic restoration of the tooth by light-curing composite material and modeling of the mucous membrane of the lateral cutter has allowed to reach high quality medical treatment. Key words: veneers, light-curing composite, correction of gingival tissue trimmer.